Upregulation of HSP90α in the lungs and circulation in sarcoidosis - Isshiki, Takuma; Sunakawa, Motoko; Vierhout, Megan; Ayoub, Anmar; Ali, Pareesa; Naiel, Safaa; Miyoshi, Shion; Naqvi, Asghar; Hambly, Nathan; Kishi, Kazuma; Ask, Kjetil; Kolb, Martin R. J. (Frontiers in Medicine, 2025)
BackgroundSarcoidosis is a systemic granulomatous disease of unknown cause. Natural improvement with favorable outcome is common, but a significant number of patients present with difficult to manage and progressive disease. The identification of biomarkers associated with disease activity and progression is warranted. Extracellular heat shock protein 90 (HSP90) α is a signaling molecule released by cells that induces proinflammatory signaling through interaction with certain receptors, such as lipoprotein receptor–related protein 1.Materials and methodsHSP90α protein expression in lung tissues derived from patients diagnosed with sarcoidosis and control subjects was assessed by immunohistochemistry. Serum HSP90α concentration was measured in sarcoidosis patients and healthy controls and correlated with clinical outcomes. Bronchoalveolar lavage fluid (BALF) was collected and analyzed for HSP90α expression. Extracellular HSP90α released from macrophages was examined in human primary cells and an immortalized cell line.ResultsMacrophages and granulomas in sarcoidosis-affected lungs showed high HSP90α expression. Serum HSP90α levels were elevated in sarcoidosis patients compared with controls and correlated with BALF HSP90α levels. HSP90α concentrations in the circulation were correlated with biomarkers of disease stage. Both primary and immortalized macrophages showed a high capacity for secreting extracellular HSP90α.ConclusionThese results demonstrate that macrophages in the lungs of sarcoidosis patients produce high levels of HSP90α, suggesting HSP90α as a potential biomarker and therapeutic target.